Suppression of Friction-Induced Stick–Slip Behavior and Improvement of Tribological Characteristics of Sliding Systems by Introducing Damping Materials. Issue 2 (3rd March 2020) - Lu, X. D.; Zhao, J.; Mo, J. L.; Wu, Y. K.; Xu, J. W; Zhang, Y. F.; Zhou, Z. R.
Abstract: An experimental study is conducted for friction systems introducing damping components consisting of different materials and different configuration. A number of experiments are performed on a pad-on-disc experimental test rig. Dynamic and tribological analyses are performed to evaluate the effects of different damping components on the stick–slip behavior. The obtained results indicate that friction systems introducing damping components of styrene butadiene rubber (SBR) or Mu-Cu damping alloy (DA) materials effectively reduce the friction-induced stick–slip behavior. The best performance was observed for the SBR damping component with a specific structure. The mechanism of introducing SBR or DA damping components into friction systems to influence the stick–slip behavior is discussed. For the SBR damping component, deformation is the dominant factor to suppress the stick–slip behavior. This is because the larger deformation of damping component could dissipate the vibration energy of friction systems and alleviate severe wear phenomena at the contact interface. For the DA damping components, the main reason for the reduction in stick–slip behavior is that the material has a higher damping capacity. Therefore, damping components of DA material only affect the vibration characteristics and not surface wear characteristics of the contact interface. The purpose of this article is to provide novel insights for the reduction or elimination of stick–slip motion at low speeds in relevant engineering applications.